Assessment of outcome of an ADHD treatment program using parent feedback - Hemamali Perera; Kamal Chandima Jeewandara; Sudharshi Seneviratne; Chandima Guruge (Sri Lanka Journal of Psychiatry, 2010)
Background Attention deficit hyperactivity disorder (ADHD) is a common behaviour disorder in children where the associated aggressive tendencies, learning difficulties and poor social skills pose a substantial burden of care on the parents. However, in traditional clinical practice, parental expectation of outcome of treatment is rarely considered. Aims This study prospectively analysed an outpatient treatment programme for children with ADHD, where parents provided feedback on the outcome of treatment. Methods Parents completed structured formats to provide information on presenting complaints, outcome at 3 months and 6 months after commencing treatment and side effects of the drug methylphenidate. Parents also attended psycho-educational and support groups.  Results Of the 102 patients, parents reported a positive outcome in the majority. There was significantly better improvement in symptoms of ADHD at 6 months when compared to 3 months of treatment (p<0.005). Also, hyperactivity improved more than attention deficit and impulsiveness at the end of 6 months, though persistence of learning difficulties (50%) and disruptive behaviour were causes for dissatisfaction about treatment. The commonest side effect was poor appetite (49%), though none of the children had identifiable weight loss. Conclusions Close involvement of parents in monitoring outcome of treatment of ADHD helps to focus on aspects of care relevant to them. DOI: 10.4038/sljpsyc.v1i2.2575 SL J Psychiatry 2010; 1 (2):51-55